IDDF2022-ABS-0128 A novel pathogen enterococcus hirae induced dysbiosis in the stomach and the genomic instability to promote gastric cancer. (2nd September 2022) - Saruuljavkhlan, Batsaikhan; Gantuya, Boldbaatar; Akada, Junko; Matsumoto, Takashi; Alfaray, Ricky Indra; Oyuntsetseg, Khasag; Yamaoka, Yoshio
Abstract : Background: Previous our microbiome analysis indicates that Enterococcus sp. predominance of microbial composition has been determined in patients with gastric cancer (GC) by 16S rRNA metagenomic analysis. We aimed to determine whether this bacterium could promote the emergence and progression of GC. Methods: The effects of E. hirae and Helicobacter pylori (clinical strain Mon-Ke2 as control) were assessed in a gastric epithelial cell line (AGS cells). The cell toxicity of AGS cells is identified by lactate dehydrogenase levels. The DNA double-strand breaks (DSBs) were assessed by gamma-H2AX expressions using immunoblotting; and single-cell gel electrophoresis (SCGE). AGS cells were analyzed for the rapid oxygen species (ROS) expressions response after E. hirae and H. pylori infections. Results: E. hirae was successfully isolated from the gastric mucosal specimen of a GC patient for the first time. The whole-genome sequence of E. hirae was confirmed by next-generation sequencing. E. hirae -infected AGS cells showed abnormal morphological changes. Infections of E. hirae and H. pylori significantly induced cell death and expression of gH2AX in AGS cells. Besides, the expression of gH2AX and DSBs was confirmed by SCGE comet formation. Interestingly, co-infection of H. pylori and E. hirae had a synergistic effect on the severity of DSBs. E. hirae could induce intranucleus and mitochondrial ROS in AGS cells same as H. pylori . We investigated whether only live E. hirae, or its released factor(s) can cause DNA damage. Supernatant from AGS cells infected with E. hirae could induce the gH2AX, whereas H. pylori required cell adhesion to induce gH2AX. The complete genome of E. hirae totally contained 2570 genes and 10 known virulence factor genes (e.g., Enterococcus pore-forming toxin). Conclusions: E. hirae- related dysbiosis in the stomach might increase the risk for GC, resulting in gained the genomic instability of gastric cells, as well as H. pylori infection. Further research investigating the impacts of this pathogen on the human host using the gastric organoid model is needed since several studies have shown that other species of Enterococcus induce cancer-promoting events resulting in DNA damage in gastric/colonic mucosa, and hepatic cells.